Contributions to the flore of Galicia, X. - Pino Pérez, Rubén; Silva Pando, Francisco Javier; Galán de Mera, Antonio; García Martínez, Xosé Ramón; Pino Pérez, Juan José; Rozados Lorenzo, María José; González Pazos, Sandra; Gómez Vigide, Fermín; Camaño Portela, José Luis; Rial Pousa, Simón; Álvarez Graña, David; B. Blanco Dios, Jaime (Botanica Complutensis, 2011)
In this study mentioned 79 different plants with interest to the flora of Galicia and other territories of the Iberian Peninsula. One of them are new records for Spain flora (Watsonia bulbillifera), 24 are regional novelties (Crassula arborescens, Teline monspessulana, Hippocrepis comosa, Chamaesyce polygonifolia, Myosotis congesta, Verbena bonariensis, Senecio pyrenaicus, Taraxacum acutangulum, T. braun-blanquetii, T. cantabricum, T. ekmanii, T. fulgidum, T. hispanicum, T. lambinonii, T. maculosum, T. pinto-silvae, T. rubicundum, T. sundbergii, Agropyrum cristatum subsp. pectinatum, Bromus inermis, Pennisetum clandestinum, Eragrostis mexicana var. virescens, Iris planifolia, Chasmanthe floribunda), 26 novedades provinciales (Ranunculus peltatus subsp. peltatus var. peltatus, Modiola caroliniana, Sedum dendroideum, Paraserianthes lophantha, Geranium purpureum, Calystegia silvatica subsp. disjuncta, Echium vulgare subsp. pustulatum, Linaria aguillonensis, Linaria lamarckii, Glechoma hederacea, Asperula aristata subsp. scabra, Taraxacum drucei, T. gallaecicum, T. marklundii, T. nordstedtii, Luzula lactea, Commelina communis, Canna indica, Cyperus involucratus, Paspalum notatum, Asphodelus fistulosus, Muscari neglectum, Veratrum album, Iris foetidissima and Hedychium gardnerianum, Passiflora caerulea). Also 15 of them are commented by its taxonomic, ecologic or chorological interest. Clypeola jonthlaspi, Alchemilla transiens, Asperula cynanchica subsp. cynanchica, Valeriana tripteris subsp. tripteris, Luzula sudetica and Rhynchos pora modesti-lucennoi are confirmed for the Galician flora. Morever, in the light of further information, we remove 6 plants from the catalog of the vascular flora of Galicia (Iberis amara, I. linifolia, Sedum sediforme, Anarrhinum laxiflorum, Asperula aristata subsp. aristata and Taraxacum palustre) and Carex vesicaria from the catalog of the Parque Nacional de las Illas Atlánticas.